(untitled) (Diyala Journal of Engineering Sciences, 2015)
A finite element method is practical and applicable for many fields including for geotechnical engineering structures. Seepage through earth dam is difficult to analyze especially dams with multiple zones. The problem becomes complex if it requires deformation analysis taking into account seismic conditions. Therefore, finite element is the best tool for analyzing seepage flow in an earth fill dam. The main objective of the paper is to simulate the seepage flow through an earth fill dam. Hassan Kanosh Dam which is located in the north eastern part of Iraq is chosen as a case study. There are three periods in the life of a dam which may be critical from the standpoint of shear failure and which must be analyzed; during construction condition, full reservoir condition, and rapid drawdown condition. The program SIGMA/W which is a finite element software coupled with SEEP/W, (another GEO-SLOPE software product) to analyze the dam. The stability analysis performed showed that all parts of the dam are safe within the prescribed rang of factors of safety for the possible loading and operation cases. It is recommended, however, that close control of the quality of the works during construction must be maintained to realize the shearing strengths necessary to fulfill the assumed strength and even more. It is recommended to check routinely the foundation conditions during excavation to realize the same end results.